(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:Mutation within the FLT 3 and NPM 1 genes ranked within the most frequent recurrent known genetic markers in acute myeloid leukemia (AML) and show apparently opposite prognostic significance. Objective:To detect the frequency of FLT3-ITD and NPM-1 mutations in Iraqi pediatric AML patients using conventional polymerized chain reaction (PCR), and to relate their prevalence with the clinical presentation and the response to induction therapy. Methods: A prospective study of 30 children presented with AML and 16 children who were age and gender matched served as negative control for the mutation. AML cases were classified according to FAB classification. WBC count, platelet count and hematocrit were measured at diagnosis and after 30 days. Molecular analysis was done on peripheral blood or bone marrow aspirate samples by conventional PCR technology. Results:FLT 3-ITD mutation was detected in 3/30 (10%) patients, whereas NPM1 mutation was detected in 4/30 (13.33%) patients. Both mutations were detected in older age patients and predominantly in male. No significant correlation between each mutation and various hematological parameters, however WBC count was significantly higher in FLT-ITD unmutated patients. FLT3-ITD mutation was detected in M3 and M3 variant whereas NPM-1 mutation was detected in M2 and M3v. The three patients having FLT-3-ITD mutation (100%) did not achieved complete hematological remission, whereas 3/24 (12.5%) patients without the mutation did not achieve remission. On the other hand 2 out of 4 (50%) patients with NPM-1 mutation had not achieved complete hematological remission and 4/22 (18.18%) patients without mutation did not achieve remission. Finally regarding the interrelation between the two mutations, the two children who had NPM1 mutation and no FLT3-ITD mutation had achieved complete remission on induction therapy whereas the three children who had FLT3-ITD mutation with or without NPM1 mutation did not achieved complete remission. Conclusion:Prevalence of FLT3-ITD and NPM-1 mutations in Iraqi pediatric AML patients is comparable to that recorded worldwide and both mutations were observed in older age children and mainly in male. FLT3-ITD mutation unlike NPM-1 mutation associate with poor response to induction therapy and the adverse effect of FLT3-ITD mutation overcome the favorable effect of NPM-1 mutation when they exist together. Keywords:Pediatric AML, Flt3-ITD mutation, NPM1 mutation, PCR